A lexicon- and construction-based approach to coordinations - Abeillé, Anne (Proceedings of the 10th International Conference on Head-Driven Phrase Structure Grammar, 2003)
Leaving aside elliptical coordinations, it is striking that no agreementhas been reached on the structure of basic coordinate constructions. Wepropose that: coordinate constructions are structurally asymmetric: the conjunctionmakes a subconstituent with one of the conjuncts. such constituents can have several functions: coordinate daughter,adjunct daughter or main clause. In order to show that some conjuncts should be analysed as adjuncts, wefocus on asymmetric cases of coordination, in which the order of theconjuncts cannot be reversed, taking examples from French, Welsh and Korean.We present an HPSG analysis which treats the <Q>coordinating</Q> conjunctions as<Q>weak</Q> heads, with lexical subtypes, and coordinate phrases as multi-headedconstructions, with different subtypes.